Impact of COVID-19 on Consumption Pattern of Vegetarians and Non-Vegetarians - Shanabhoga, M. B.; Govindaraj, Gurrappanaidu; Naveenkumar, G. S.; Swamy, H. M.; Bheemappa, Mahantheshwara; Nagalingam, M.; Shome, B. R.; Rahman, Habibar (Indian Journal of Extension Education, 2022)
The aim of this study was to investigate the impacts of COVID-19 on the consumption patterns of vegetarians and non-vegetarian populations, mainly on animal-based products. A cross-sectional, questionnaire-based survey was conducted among the urban and peri urban populations of Bengaluru, Karnataka during October to November of 2020 through electronic mode. The data was collected from 837 (54.2% non-vegetarian and 54.2% vegetarians) participants. Significant change in the number of family members before and during the COVID lockdown was observed. The egg and chicken consumption had drastically increased among the non-vegetarians whereas, among the majority of the vegetarians, no change in milk consumption but a considerable increase in curd and buttermilk, paneer/cheese, and ghee/butter consumption was observed. Both non-vegetarian and vegetarian consumers had shifted to online delivery apps for purchasing products during the pandemic. The majority of the non-vegetarians (80.84%) and vegetarians (55.09%) opined that the price of meat and milk products increased during the pandemic. The pandemic had an effect on consumption among non-vegetarian and vegetarian consumers but increased accessibility of products through deliveries or pick-up points at various locations might have reduced the price and also induce the consumption of these products.
Keywords: COVID-19; Consumption pattern; Vegetarians; Non-vegetarians; Food security; Food choice